Variable and Self-Service Costs in Reciprocal Allocation Models. - Kaplan, Robert S. (The Accounting Review, 1973)
The article investigates the properties of the reciprocal service department cost allocation model. The first and most important investigation assumes that all service department costs are variable and determines how to compute the marginal cost of supplying additional units of output from each service department. First, when allocating variable costs, the final costs should be useful for management decisions by representing the incremental costs of supplying given levels of outputs from the service departments. Second, when service departments also provide some service to themselves, it seems that the allocations to other departments should not be affected by the treatment of the self-service cost. Therefore it might prove useful for organizations with limited access to computational facilities or with an extremely large number of interacting service departments where the matrix inversion on a computer might be time consuming and subject to considerable round-off error. In conclusion, it is awkward to have allocation methods yield different results depending on the treatment of self-service costs. The allocations should depend upon the properties of the interaction terms in the matrices and not on the treatment of the self-service cost.